Nitrative Stress and Auditory Dysfunction - Monazza Shahab; Samson Jamesdaniel (MDPI AG, 2022)
Nitrative stress is increasingly recognized as a critical mediator of apoptotic cell death in many pathological conditions. The accumulation of nitric oxide along with superoxide radicals leads to the generation of peroxynitrite that can eventually result in the nitration of susceptible proteins. Nitrotyrosine is widely used as a biomarker of nitrative stress and indicates oxidative damage to proteins. Ototoxic insults, such as exposure to noise and ototoxic drugs, enhance the generation of 3-nitrotyrosine in different cell types in the cochlea. Nitrated proteins can disrupt critical signaling pathways and eventually lead to apoptosis and loss of sensory receptor cells in the cochlea. Accumulating evidence shows that selective targeting of nitrative stress attenuates cellular damage. Anti-nitrative compounds, such as peroxynitrite decomposition catalysts and inducible nitric oxide synthase inhibitors, prevent nitrative stress-mediated auditory damage. However, the role of nitrative stress in acquired hearing loss and its potential significance as a promising interventional target is yet to be fully characterized. This review provides an overview of nitrative stress mechanisms, the induction of nitrative stress in the auditory tissue after ototoxic insults, and the therapeutic value of targeting nitrative stress for mitigating auditory dysfunction.